Stock Portfolio Risk and Return: Indonesia vs. China During Covid-19: Perbandingan Risiko dan Pengembalian Portofolio Saham: Indonesia vs. China Selama Pandemi Covid-19 dengan Menggunakan Model Indeks Tunggal - Agusti Marini; Wiwit Hariyanto (Academia Open, 2024)
This study aimed to compare the expected return and risk of stock portfolios in Indonesia and China during the Covid-19 pandemic using the Single Index Model. The study used a quantitative approach with a sample of IDX30 stocks listed on the Indonesian Stock Exchange and SSE50 stocks listed on the Shanghai Stock Exchange. The data were analyzed using the Single Index Model with Microsoft Excel 2010 and the independent sample t-test with SPSS 23. The results showed that four stocks in Indonesia and ten stocks in China met the criteria for forming an optimal stock portfolio using the Single Index Model. The study also found a difference in the expected return and risk of stock portfolios between Indonesia and China. This study implies that investors should consider the Single Index Model and the differences in expected return and risk when making investment decisions in the Indonesian and Chinese stock markets during the Covid-19 pandemic.Highlights : The Single Index Model is an effective tool for forming optimal stock portfolios during the Covid-19 pandemic in Indonesia and China. The study compares the expected return and risk of stock portfolios in Indonesia and China using the Single Index Model. The study highlights the importance of considering the differences in expected return and risk when making investment decisions in the Indonesian and Chinese stock markets during the Covid-19 pandemic. Keywords: stock portfolio, Single Index Model, Covid-19 pandemic, Indonesia, China.